Histological Examination of Lemongrass Resorbable Dressing on Gingival Healing after Gingivectomy in Rats - Amaliya, Amaliya; Budhirahardjo, Indri; Hendiani, Ina (European Journal of Dentistry, 2022)
Objectives The present work aimed to evaluate the effect of lemongrass extract incorporated in a resorbable periodontal dressing on gingival wound healing microscopically, following gingivectomy in rats.Materials and Methods Thirty healthy adult male Sprague–Dawley rats were used in this study. Gingivectomy was performed on anterior area of lower jaw in the labial surface of central incisive and, subsequently, wound areas were covered with povidone iodine gel (group P, positive control, n = 10), lemongrass resorbable dressing (group L, n = 10), and a cellulose-based dressing containing myrrh (group M, positive control, n = 10). Histological changes were monitored in days 4, 7, and 14 postsurgery to evaluate fibroblast and collagen deposition as repair stage of healing process.Statistycal Analysis One-way analysis of variance (ANOVA) followed by Tukey's post hoc for multiple comparisons were employed to measure differences between pairs of means, p-value of 0.05 was considered statistically significant.Results We observed significant difference repair parameters of the healing process between surgical sites treated with lemongrass periodontal dressing and control groups. Wounds treated with lemongrass dressing had greater fibroblast compared with control groups in 4 and 7 days after surgery (p ≤ 0.05).Conclusion The results suggest positive potential therapeutic effects for this new formulation of periodontal dressing on acceleration of surgical wound healing that lead to improvement of periodontal treatment consequences following gingivectomy.
Keywords: lemongrass; dressing; wound healing; gingivectomy